Wheat, barley and corn silage rations for growing yearling steers - K.K. Bolsen; L.L. Berger; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1975)
Seven silage and ration treatments compared were: (1) Paoli barley, (2) Arthur wheat, (3) Parker wheat, (4) Parker-head wheat, (5) Parker-head wheat and corn silage (equal parts), (6) corn silage plus a soybean meal supplement, (7) corn silage plus a urea supplement. Treatments 1 through 5 included a soybean meal supplement.
Keywords: Cattlemen& #x27; s Day; 1975; Report of progress (Kansas State University. Agricultural Experiment Station); 230; Beef; Wheat; Barley; Corn silage; Steers